Visual Exploration of Dynamic or Static Joint Attention Bids in Children With Autism Syndrome Disorder - Cilia, Federica; Aubry, Alexandre; Le Driant, Barbara; Bourdin, Beatrice; Vandromme, Luc (Frontiers in Psychology, 2019)
Eye-tracking studies have revealed a specific visual exploration style characterizing individuals with Autism Spectrum Disorder (ASD). The aim of this study is to investigate the impact of stimulus type (static vs. dynamic) on visual exploration in children with ASD. Twenty-eight children with ASD, 28 children matched for developmental communication age and 28 children matched for chronological age watched a video and a series of photos involving the same joint attention scene. For each stimulus, Areas of Interest (AOI) were determined based on Voronoi diagrams, which were defined around participants’ fixation densities, defined by the mean shift algorithm. To analyze the eye-tracking data on visual exploration, we used a method for creat-ing AOI a posteriori, based on participants’ actual fixations. The results showed the value of both kinds of stimuli. The photos allowed for the identification of more precise AOI, and show similarities in exploration between ASD and typical children. On the other hand, in video, among ASD children only, there are few differences in the way they look at the target depend-ing on the deictic cue used. This raises questions regarding their understanding of a joint atten-tion bid recorded on a video. Finally, whatever the stimulus, pointing seems to be the most im-portant element for children to look at the target.